Light soft porcelain material for wall decoration and preparation process thereof

By making homemade crosslinking fillers, the crosslink density and three-dimensional network structure of soft porcelain materials are enhanced, and the problems of bulky and easy damage and unstable adhesion of traditional decorative materials are solved, achieving higher mechanical strength and impact resistance.

CN119822747APending Publication Date: 2025-04-15ZHONGSHAN YATU PAINT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510135548.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional wall decoration materials are bulky and easy to break, and unstable adhesion in environments with high temperature and humidity shear stress, which poses safety hazards, and poor breathability and freeze cracks are prone to occur.

Method used

The polycarboxylic monomer and methylpropylene glycol were prepared by homemade crosslinking fillers and used for the preparation of polyhydroxy monomers through octphenyl-cage polysilsesquioxane, and the hyperbranched organosilane resin was prepared in combination with ethyl orthosilicate, thereby enhancing the crosslinking density and three-dimensional network structure.

Benefits of technology

It significantly improves the mechanical strength, impact strength and performance of soft porcelain materials that are not prone to cracking, enhances the stability and dispersion of the materials, and improves the use effect of decorative materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822747A_ABST
    Figure CN119822747A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soft porcelain materials, and discloses a lightweight soft porcelain material for wall decoration and a preparation process thereof, the lightweight soft porcelain material comprises the following raw materials: 100-120 parts of a modified aqueous acrylic emulsion, 40-50 parts of Portland cement, 1-3 parts of an antioxidant, 1-3 parts of a flame retardant, 20-30 parts of a crosslinking filler and 1-3 parts of a foaming agent; the preparation process of the light soft porcelain material comprises the following steps: preparing hyperbranched organosilane resin by adopting a self-made polyhydroxy monomer and tetrapropyl orthosilicate, generating a cross-linked filler, uniformly mixing the cross-linked filler with the modified water-based acrylic emulsion, the Portland cement liquid, the antioxidant, the flame retardant and the foaming agent, pouring into a mold, and drying at 90-100 DEG C for 4-5 hours to obtain the light soft porcelain material. The light soft porcelain material for wall decoration is obtained. The preparation method has the beneficial technical effect of remarkably enhancing the mechanical strength of the soft porcelain material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft porcelain materials, in particular to a light soft porcelain material for wall decoration and a preparation process thereof. Background Art

[0002] Traditional decorative materials are relatively heavy, such as ceramic tiles and marble. These decorative materials require very high labor requirements when they are manually processed and attached to the wall, and are easily damaged during processing. When attached, due to their heavy weight, they are easily detached from the wall due to their own gravity, which poses a safety hazard. The temperature and humidity shear stress of ceramic tiles is relatively large, which to a large extent affects and interferes with the safety of tile attachment. In addition, the air permeability of ceramic tiles is relatively poor, and in winter, they are very prone to freezing and cracking. Metal and glass curtain walls can also be used as the finishing layer of the exterior wall insulation system. Due to the high complexity of the installation process and the high cost of the materials, these materials have not been fully popularized and promoted in the actual development process.

[0003] As a new type of building finishing material, soft porcelain has the advantages of good flexibility, light weight, multiple colors and shapes, energy saving and environmental protection, and has become one of the focuses of research and development in the field of green building materials in the world. Soft porcelain is made of water-based resin, industrial tailings, construction waste, stone powder, glass fiber and other materials, and is made into a slurry with a certain fluidity through high-speed uniform dispersion, curve drying and shaping. At present, how to improve the mechanical properties of soft porcelain materials is the current technical focus. Summary of the invention

[0004] The present invention provides a lightweight soft porcelain material for wall decoration and a preparation process thereof, which realizes the technical goal of increasing the cross-linking density of organic and inorganic substances through a self-made cross-linked filler. Compared with other soft porcelain materials, the material has more excellent mechanical strength and impact strength, and has the excellent performance of not being easy to crack.

[0005] A lightweight soft porcelain material for wall decoration, comprising the following raw materials in parts by weight: 100-120 parts of modified water-based acrylic emulsion, 40-50 parts of Portland cement, 1-3 parts of antioxidant, 1-3 parts of flame retardant, 20-30 parts of cross-linked filler and 1-3 parts of foaming agent;

[0006] The cross-linked filler comprises the following steps:

[0007] Under normal temperature conditions, 4-6 parts of octaphenyl-cage polysilsesquioxane and 180-220 parts of iron powder are added to a reaction kettle by weight, 40-60 parts of dichloromethane are added, stirred, 2-4 parts of bromine water are added dropwise, stirring is continued, and 70-90 parts of 8-10wt% NaHSO3 aqueous solution are added to obtain intermediate 1;

[0008] Under nitrogen conditions, 4-6 parts of the intermediate 1 obtained in step S1 and 90-110 parts of freshly distilled THF are added to a reaction kettle by weight, stirred, cooled with liquid nitrogen to -78, 8-12 parts of a 1.8-2 mol / L n-butyl lithium n-hexane solution are added dropwise, and the addition is completed within 0.5-1 h. At room temperature, 2-4 parts of dry ice are added, and 20-30 parts of 1-2 mol / L hydrochloric acid are added, and stirring is continued to obtain a polycarboxyl monomer;

[0009] Under nitrogen protection, 2-5 parts of a polycarboxyl monomer and 30-50 parts of methyl propanediol are mixed in a reaction kettle by weight, the temperature is raised to 70-80° C., condensed and refluxed, stirring is started, the temperature is raised to 135-145° C., and the temperature is kept for 7-8 hours, the temperature is raised to 190-210° C. at a rate of 4-5° C. / min, and the temperature is kept for 1-2 hours, 0.2-0.4 parts of tetrabutyl titanate are added, and the temperature is kept for 4-5 hours, and the temperature is cooled to room temperature, 2-3 parts of ethylene glycol and 1-2 parts of pentaerythritol are added, and the temperature is stirred to obtain a polyhydroxy monomer;

[0010] Under normal temperature and nitrogen conditions, 40-60 parts of tetrapropyl orthosilicate and 2-4 parts of polyhydroxy monomers are mixed by weight, a distillation device is added, stirred, the temperature is raised to 160-170° C., kept warm for 1-2 hours, the temperature is reduced to 95-105° C., 2-3 parts of tert-butyl peroxy-2-ethylhexanoate are added, the reaction temperature is raised to 160-170° C., the distillate is evaporated, kept warm, the distillation temperature is reduced to 45-55° C., the heating is turned off, the distillation is cooled, and the fraction is removed to obtain a hyperbranched organosilane resin;

[0011] Put 6-8 parts of expanded vermiculite by weight into an oven at 40-50°C for drying, add 20-40 parts of anhydrous ethanol at 70-80°C for stirring, add 10-12 parts of hyperbranched organosilane resin and 0.1-0.2 parts of ammonia water, stir, and ultrasonicate to obtain a cross-linked filler.

[0012] Preferably, the modified aqueous acrylic emulsion comprises the following steps:

[0013] Under nitrogen protection, heat 20-30 parts of epoxy resin and 10-20 parts of waterborne polyurethane resin by weight to 105-115°C, add 1-2 parts of p-hydroxyanisole, stir for 5-10 hours, cool to 85-95°C, add 100-120 parts of waterborne acrylic emulsion drop by drop within 0.5-1 hour, stir for 7-8 hours, cool to room temperature to obtain modified waterborne acrylic emulsion.

[0014] Preferably, the antioxidant is any one of 2,6-di-tert-butyl-p-cresol, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 2,5-di-tert-butylhydroquinone.

[0015] Preferably, the flame retardant is any one of antimony trioxide, magnesium hydroxide and aluminum hydroxide.

[0016] Preferably, the foaming agent is any one of water glass, aluminum silicate and ammonium bicarbonate.

[0017] A process for preparing a lightweight soft porcelain material for wall decoration comprises the following steps:

[0018] Step 1: at room temperature, add silicate cement to the modified waterborne acrylic emulsion by weight, stir, heat to 80-90° C., add cross-linked filler, stir under reduced pressure for 1-2 hours, cool to 65-75° C., add water, foaming agent, antioxidant and flame retardant, stir to obtain a material;

[0019] Step 2: pour the material into a mold, place the mold in an oven at a temperature of 90-100° C., dry for 4-5 hours, and cool to obtain a lightweight soft porcelain material for wall decoration.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] Octaphenyl-cage polysilsesquioxane is used to prepare a polycarboxyl monomer, which is reacted with methyl propylene glycol to generate a polyhydroxy monomer. The polyhydroxy monomer is used as a modified component and reacted with ethyl orthosilicate to prepare a hyperbranched organosilane resin. The ethyl orthosilicate is heated to generate silanol, which can be covalently bonded to itself and dehydrated and condensed with the polyhydroxy monomer to form a covalent bond to generate a hyperbranched organosilane resin with a cross-linked network. Octaphenyl-cage polysilsesquioxane itself is a highly cross-linked material with rich active groups on the surface, which increases the hyperbranching degree and cross-linking density of the hyperbranched organosilane, strengthens the three-dimensional network structure of the hyperbranched organosilane resin itself, promotes the close combination of various components, and significantly improves the mechanical strength of the system.

[0022] The hyperbranched organosilane resin is hydrolyzed in an alkaline alcohol aqueous solution to generate Si-OH groups, and the surface of expanded vermiculite contains a large number of hydroxyl groups. The Si-OH groups on the surface of the hyperbranched organosilane resin react with the -OH groups on the surface of the expanded vermiculite to form a stable covalent bond, so that the expanded vermiculite and the organosilane resin form a stable structure, effectively reducing the agglomeration between the expanded vermiculite particles and improving the dispersibility of the expanded vermiculite in the soft porcelain material.

[0023] After the hyperbranched organosilane resin is combined with expanded vermiculite, it is added to the modified acrylic emulsion. The hyperbranched organosilane resin and the modified acrylic emulsion form an interpenetrating network structure, which increases the cross-linking of inorganic materials, thereby increasing the mechanical strength of the system.

[0024] In the modified acrylic emulsion, on the one hand, epoxy resin and water-based acrylic emulsion are used for graft copolymerization, and on the other hand, epoxy resin and water-based polyurethane resin are used for graft copolymerization. The network structure of the formed copolymer resin can further improve the cross-linking degree of the system, thereby improving the mechanical properties of the system.

[0025] The invention effectively overcomes the shortcomings of easy migration and uneven dispersion of inorganic materials, effectively enhances the stability and mechanical strength of the system, and improves the use effect of soft porcelain decorative materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of the impact strength of the lightweight soft ceramic material for wall decoration obtained by Example 4 and Comparative Example 1 under different conditions;

[0027] Figure 2 The following is a comparison chart of the tensile strength of the lightweight soft ceramic material for wall decoration obtained by Example 4 and Comparative Example 1 under different conditions. DETAILED DESCRIPTION

[0028] Embodiment 1:

[0029] A lightweight soft porcelain material for wall decoration, comprising the following raw materials in parts by weight:

[0030] Modified water-based acrylic emulsion, 110 parts;

[0031] Portland cement, 55 parts;

[0032] Antioxidant - 2,6-di-tert-butyl-p-cresol, 2 parts;

[0033] Flame retardant - antimony trioxide, 2 parts;

[0034] Cross-linked filler, 25 parts;

[0035] Foaming agent - water glass, 2 parts;

[0036] Portland cement was purchased from Guangxi Yufeng Cement Co., Ltd., model P·Ⅱ-42.5R;

[0037] Antimony trioxide was purchased from Henan Yiquan Chemical Technology Co., Ltd. with a particle size of 5 μm;

[0038] Water glass was purchased from Jinan Mingchuan Chemical Co., Ltd. with a modulus of 2 and a CAS number of 215-687-4.

[0039] Embodiment 2:

[0040] The preparation method of the modified waterborne acrylic emulsion in Example 1 is:

[0041] Under nitrogen protection, 15 parts of epoxy resin and 25 parts of waterborne polyurethane resin were added to a reaction kettle, the temperature was raised to 105°C, 1.5 parts of p-hydroxyanisole were added, stirred for 5 hours, cooled to 85°C, 100 parts of waterborne acrylic emulsion were added dropwise for 0.5 hours, stirred for 8 hours, and cooled to room temperature to obtain a modified waterborne acrylic emulsion;

[0042] The epoxy resin was purchased from Shandong Dayi Chemical Co., Ltd., model number E51;

[0043] Waterborne polyurethane resin was purchased from Dawei Huatai New Material Technology Co., Ltd., model AH-1730;

[0044] The water-based acrylic emulsion was purchased from Huizhou Qisheng Technology Co., Ltd., model K-167;

[0045] Among them, on the one hand, epoxy resin and water-based acrylic emulsion are used for graft copolymerization, and on the other hand, epoxy resin and water-based polyurethane resin are used for graft copolymerization. The network structure presented by the formed copolymer resin can improve the stability and cross-linking degree of the system.

[0046] Embodiment 3:

[0047] The preparation method of the cross-linked filler in Example 1 is:

[0048] Step S1, under normal temperature conditions, add 5 parts of octaphenyl-cage polysilsesquioxane and 200 parts of iron powder to a reactor, add 50 parts of dichloromethane, stir for 20 minutes, add 3 parts of bromine water dropwise, stir for 24 hours, add 80 parts of a 10% NaHSO3 aqueous solution, terminate the reaction, let stand for stratification, wash the organic phase with water 3 times, rotary evaporate, dry, add 2 parts of ethyl acetate, add 400 parts of methanol, precipitate, repeat sedimentation 3 times, dry to obtain intermediate 1;

[0049] Octaphenyl-cage polysilsesquioxane was purchased from Forsman Technology (Beijing) Co., Ltd., CAS No. 5256-79-1;

[0050] Step S2, under nitrogen conditions, add 5 parts of the intermediate 1 obtained in step S1 and 100 parts of freshly distilled THF into a reactor, stir, cool with liquid nitrogen to -78°C, add dropwise 10 parts of 2 mol / L n-butyl lithium n-hexane solution, the addition time is 0.5h, stir for 3h, add 3 parts of dry ice, react at room temperature for 12h; slowly add dropwise 25 parts of 2 mol / L hydrochloric acid to terminate the reaction; extract, wash, dry, concentrate, wash 5 times with a mixed solution of ethyl acetate: hexane (1:10), dry, and obtain a polycarboxyl monomer;

[0051] Step S3, under nitrogen protection, 4 parts of a polycarboxyl monomer and 40 parts of methyl propylene glycol are mixed in a reaction kettle, heated to 80° C., condensed and refluxed, stirring is started, the temperature is raised to 145° C., and the temperature is kept for 8 hours; the temperature is raised to 210° C. at a rate of 5° C. / min, and the temperature is kept for 2 hours; 0.3 parts of tetrabutyl titanate are added, the temperature is kept for 4 hours, the temperature is cooled to room temperature, 2.5 parts of ethylene glycol and 1.5 parts of pentaerythritol are added, and the temperature is stirred for 30 minutes to obtain a polyhydroxy monomer;

[0052] Step S4, at room temperature and nitrogen, 50 parts of tetrapropyl orthosilicate and 3 parts of polyhydroxy monomer are mixed, a distillation device is added, and the mixture is stirred for 30 minutes. The temperature is raised to 170° C., kept warm for 1 hour, then lowered to 105° C., 2.5 parts of tert-butyl peroxy-2-ethylhexanoate are added, and the temperature is raised until distillate is evaporated. The reaction temperature is raised to 160° C., kept warm, the distillation temperature is lowered to 55° C., the heating is turned off, and the mixture is cooled to obtain a hyperbranched organosilane resin;

[0053] Step S5, putting 7 parts of expanded vermiculite into an oven, drying for 2 hours at a drying temperature of 50°C, cooling, adding to 30 parts of anhydrous ethanol, ultrasonicating for 10 minutes, stirring for 6 hours at a stirring temperature of 80°C, adding 10 parts of hyperbranched organosilane resin and 0.1 part of ammonia water, stirring for 30 minutes, ultrasonicating for 10 minutes, filtering 3 times, washing 3 times, putting into a vacuum drying oven, drying, and crushing to obtain a cross-linked filler.

[0054] The expanded vermiculite was purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd., with a particle size of 30 μm;

[0055] Before the expansion vermiculite is modified, the surface polarity is large. After stirring, local agglomeration easily occurs in the system, and the degree of dispersion is not ideal. After the expansion vermiculite system is combined with the hyperbranched organosilane resin silane, it is relatively stable, without stratification, and evenly dispersed. The two substances are well compatible, the steric hindrance is increased, the agglomeration between particles is effectively reduced, and the dispersion is improved;

[0056] Hyperbranched organosilane resin is hydrolyzed in alkaline alcohol-water solution to generate Si-OH groups, and self-condensation occurs first between Si-OH groups. Expanded vermiculite surface contains a large number of hydroxyl groups, and uncondensed Si-OH groups form hydrogen bonding forces with -OH groups on the surface of expanded vermiculite. Si-OH groups and -OH groups dehydrate and condense to form stable covalent bonds, so that expanded vermiculite and organosilane resin form a stable structure, effectively reducing the agglomeration between particles and improving dispersibility; hyperbranched organosilane resin itself has a three-dimensional network structure, which is connected with expanded vermiculite, further increasing the stability of the system, further enhancing the stability of the system and the adhesion of expanded vermiculite. After the expanded vermiculite is combined with the hyperbranched organosilane resin, the surface polarity also effectively reduces the water absorption of the system and increases the waterproofness of the system.

[0057] Embodiment 4:

[0058] Example 1 The preparation process of the lightweight soft porcelain material for wall decoration is as follows:

[0059] Step 1: Add silicate cement to the modified waterborne acrylic emulsion, stir at room temperature for 2 hours, heat to 90°C, add cross-linked filler, reduce pressure, stir for 1 hour, cool to 75°C, add water, water glass, 2,6-di-tert-butyl-p-cresol and antimony trioxide, stir for 30 minutes, and obtain a material;

[0060] Step 2: pour the material into a mold, place the mold in an oven, set the oven temperature to 90° C., bake for 5 hours, cool and dry, and obtain a lightweight soft porcelain material for wall decoration.

[0061] Comparative Example 1:

[0062] A lightweight soft porcelain material for wall decoration, comprising the following raw materials in parts by weight:

[0063] Modified waterborne acrylic emulsion, 120 parts;

[0064] Portland cement, 55 parts;

[0065] Antioxidant - 2,6-di-tert-butyl-p-cresol, 2 parts;

[0066] Flame retardant - antimony trioxide, 2 parts;

[0067] Expanded vermiculite, 7 parts;

[0068] Foaming agent - water glass, 2 parts;

[0069] Portland cement was purchased from Guangxi Yufeng Cement Co., Ltd., model P·Ⅱ-42.5R;

[0070] Expanded vermiculite was purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd. with a particle size of 30 μm;

[0071] Fly ash was purchased from Shijiazhuang Xunluo New Material Technology Co., Ltd. It is a first-class product with a particle size of 10 μm and a specific surface area of ​​350 m 2 / kg;

[0072] Antimony trioxide was purchased from Henan Yiquan Chemical Technology Co., Ltd. with a particle size of 5 μm;

[0073] Water glass was purchased from Jinan Mingchuan Chemical Co., Ltd., with a modulus of 2 and a CAS number of 215-687-4;

[0074] The preparation process of the above-mentioned lightweight soft porcelain material for wall decoration is as follows:

[0075] Step S1, under nitrogen protection, add 15 parts by weight of epoxy resin and 25 parts by weight of waterborne polyurethane resin into a reaction kettle, heat to 105° C., add 1.5 parts by weight of p-hydroxyanisole, stir for 5 hours, cool to 85° C., drop 110 parts by weight of waterborne acrylic emulsion, the drop adding time is 0.5 hours, stir for 8 hours, cool to room temperature, and obtain a modified waterborne acrylic emulsion;

[0076] Step S2, adding silicate cement to the modified water-based acrylic emulsion, stirring at room temperature for 2 hours, heating to 90° C., stirring under reduced pressure, stirring for 1 hour, cooling to 75° C., adding water, expanded vermiculite, water glass, 2,6-di-tert-butyl-p-cresol and antimony trioxide, stirring for 30 minutes, and obtaining a material;

[0077] Step S3, pouring the material into a mold, placing the mold in an oven at 90° C. for 5 hours, cooling and drying to obtain a soft porcelain decorative material.

[0078] Performance Testing

[0079] The soft ceramic materials for wall decoration prepared in Example 4 and Comparative Example 1 were subjected to the following tests respectively.

[0080] 1. Impact strength test

[0081] According to the JG / T540-2017 standard, the soft ceramic materials for wall decoration of Example 4 and Comparative Example 1 were coated on the test panels respectively and cured for 7 days. The test panel was placed flat on the base by the impact tester using a positive impact, and different heights were adjusted. The hammer controller was pressed to make the hammer head fall freely; the test panel was taken out to observe whether the coating had cracks, and the height of the cracks in the coating was recorded; the test panel was coated in the same way, and the coating was placed in a xenon lamp weathering test box. After 1200 hours, it was taken out and the impact strength test was performed, and the height of the cracks in the coating was recorded;

[0082] The test results are as follows Figure 1 As shown, compared with Comparative Example 1, under normal conditions and xenon lamp aging conditions, the crack height of the product of Example 4 is larger, which proves that the impact strength is better. The possible mechanism is that cross-linked fillers are added to the soft porcelain material for wall decoration in Example 4, which increases the cross-linking density of the system, promotes close connection of the components, and improves the impact strength of the system.

[0083] 2. Tensile strength test

[0084] According to GB / T528-2009 standard, a tensile testing machine, model JY-L-200, was used. First, the soft ceramic materials for wall decoration of Example 4 and Comparative Example 1 were cut into dumbbell-shaped specimens, and the tensile testing machine was debugged. The tensile test was performed at a rate of 50 mm / min. The tests were performed at 25°C and 0°C respectively, and the tensile strength of each sample was recorded.

[0085] The test results are as follows Figure 2 As shown, compared with Comparative Example 1, at low temperature and room temperature, the tensile strength of the product of Example 4 is greater, and the mechanical strength is significantly better than that of the product of Comparative Example 1. The possible mechanism is that cross-linked fillers are added to the soft porcelain material for wall decoration in Example 4, which increases the cross-linking density of the system, improves the toughness of the system, and increases the tensile strength of the system.

Claims

1. A lightweight soft porcelain material for wall decoration, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of modified water-based acrylic emulsion, 40-50 parts of silicate cement, 1-3 parts of antioxidant, 1-3 parts of flame retardant, 20-30 parts of cross-linked filler and 1-3 parts of foaming agent; The cross-linked filler comprises the following steps: Step S1, under normal temperature, 4-6 parts of octaphenyl-cage polysilsesquioxane and 180-220 parts of iron powder are added to a reaction kettle by weight, 40-60 parts of dichloromethane are added, stirred, 2-4 parts of bromine water are added dropwise, stirring is continued, and 70-90 parts of 8-10wt% NaHSO3 aqueous solution are added to obtain intermediate 1; Step S2, under nitrogen conditions, 4-6 parts of the intermediate 1 obtained in step S1 and 90-110 parts of freshly distilled THF are added to a reaction kettle by weight, stirred, cooled with liquid nitrogen to a temperature of -78°C, 8-12 parts of a 1.8-2 mol / L n-butyl lithium n-hexane solution are added dropwise, the addition is completed over 0.5-1 h, 2-4 parts of dry ice are added at room temperature, 20-30 parts of 1-2 mol / L hydrochloric acid are added, and stirring is continued to obtain a polycarboxyl monomer; Step S3, under nitrogen protection, 2-5 parts of a polycarboxyl monomer and 30-50 parts of methyl propanediol are mixed in a reaction kettle by weight, the temperature is raised to 70-80° C., condensed and refluxed, stirring is started, the temperature is raised to 135-145° C., and the temperature is kept for 7-8 hours, the temperature is raised to 190-210° C. at a rate of 4-5° C. / min, and the temperature is kept for 1-2 hours, 0.2-0.4 parts of tetrabutyl titanate are added, and the temperature is kept for 4-5 hours, and the temperature is cooled to room temperature, 2-3 parts of ethylene glycol and 1-2 parts of pentaerythritol are added, and the temperature is stirred to obtain a polyhydroxy monomer; Step S4, at room temperature and nitrogen, 40-60 parts of tetrapropyl orthosilicate and 2-4 parts of polyhydroxy monomers are mixed by weight, a distillation device is added, stirred, the temperature is raised to 160-170° C., kept warm for 1-2 hours, the temperature is reduced to 95-105° C., 2-3 parts of tert-butyl peroxy-2-ethylhexanoate are added, the reaction temperature is raised to 160-170° C., the distillate is evaporated, the temperature is kept warm, the distillation temperature is reduced to 45-55° C., the heating is turned off, the distillation is cooled, and the fraction is removed to obtain a hyperbranched organosilane resin; Step S5, putting 6-8 parts of expanded vermiculite by weight into an oven at a temperature of 40-50° C., drying, adding 20-40 parts of anhydrous ethanol at a temperature of 70-80° C., stirring, adding 10-12 parts of hyperbranched organosilane resin and 0.1-0.2 parts of ammonia water, stirring, and ultrasonicating to obtain a cross-linked filler.

2. A lightweight soft porcelain material for wall decoration according to claim 1, characterized in that: The modified water-based acrylic emulsion comprises the following steps: Under nitrogen protection, heat 20-30 parts of epoxy resin and 10-20 parts of waterborne polyurethane resin by weight to 105-115°C, add 1-2 parts of p-hydroxyanisole, stir for 5-10 hours, cool to 85-95°C, add 100-120 parts of waterborne acrylic emulsion drop by drop within 0.5-1 hour, stir for 7-8 hours, cool to room temperature to obtain modified waterborne acrylic emulsion.

3. A lightweight soft porcelain material for wall decoration according to claim 1, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-p-cresol, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 2,5-di-tert-butylhydroquinone.

4. A lightweight soft porcelain material for wall decoration according to claim 1, characterized in that: The flame retardant is any one of antimony trioxide, magnesium hydroxide and aluminum hydroxide.

5. The lightweight soft porcelain material for wall decoration according to claim 1, characterized in that: The foaming agent is any one of water glass, aluminum silicate and ammonium bicarbonate.

6. A process for preparing a lightweight soft ceramic material for wall decoration as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: at room temperature, add silicate cement to the modified waterborne acrylic emulsion by weight, stir, heat to 80-90° C., add cross-linked filler, stir under reduced pressure for 1-2 hours, cool to 65-75° C., add water, foaming agent, antioxidant and flame retardant, stir to obtain a material; Step 2: pour the material into a mold, place the mold in an oven, dry at 90-100° C. for 4-5 hours, and cool to obtain a lightweight soft porcelain material for wall decoration.